2019
DOI: 10.1002/jmri.26657
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter diffusion‐weighted imaging for characterizing pathological patterns in lupus nephritis patients: A preliminary study

Abstract: Background Microstructural changes of lupus nephritis (LN) kidney such as inflammatory cell infiltration or fibrosis could influence water molecular movement or diffusion, which indicates that diffusion‐weighted imaging (DWI) may become a valuable tool in evaluation of this disease. Purpose To explore whether multiparameter diffusion‐weighted imaging (mDWI) could contribute to characterize pathological patterns in LN patients. Study Type Retrospective. Population Twenty‐two patients with LN. Field Strength/Seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…These deposits had access to the vascular space and may activate circulating myeloid cells that express FC receptors, allowing them to infiltrate the renal tissue. By contrast, subepithelial deposits, found in Class V disease, injure podocytes but elicit a less severe inflammatory response, as they contacted only the urinary space [ 9 ]. Pairwise comparisons of the type II, III, and IV groups showed significant differences, which also conform to the most obvious characteristic of type IV LN activity.…”
Section: Discussionmentioning
confidence: 99%
“…These deposits had access to the vascular space and may activate circulating myeloid cells that express FC receptors, allowing them to infiltrate the renal tissue. By contrast, subepithelial deposits, found in Class V disease, injure podocytes but elicit a less severe inflammatory response, as they contacted only the urinary space [ 9 ]. Pairwise comparisons of the type II, III, and IV groups showed significant differences, which also conform to the most obvious characteristic of type IV LN activity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it is known that D is determined by higher b values (>100 s/mm 2 ), while D* is significantly influenced by lower b values. The number of b values used in the literature ranges from 1 to 16 (31), with strength generally no more than 1,500 s/mm 2 (32).…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, a study first reported the feasibility of DKI in the kidneys of healthy volunteers [ 18 ]. Over the past decade, numerous studies have investigated the application of DKI in kidney diseases to assess renal injury, such as renal tumors [ 19 21 ], acute kidney injury from various causes [ 12 , 22 , 23 ], chronic kidney disease [ 13 , 24 , 25 ], diabetic nephropathy [ 12 , 26 , 27 ], IgA nephropathy [ 28 , 29 ], and lupus nephritis [ 30 ]. However, few studies have applied DKI to assess renal injury in patients with PA.…”
Section: Introductionmentioning
confidence: 99%